1992
DOI: 10.1177/112067219200200108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia in Open Angle Glaucoma

Abstract: In this study concerning the prevalence of myopia in patients with open angle glaucoma, its distribution was analyzed within the sample tested in relation to the refraction defect size, compared with a control group of non-glaucomatous myopic subjects. The overall myopic rate was 17.2% of the glaucomatous patients; high myopia was more frequent in the subjects with open angle glaucoma (p less than 0.001) than in the myopic patients, thus appearing as a possible risk factor for the development of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…A population-based study in Wisconsin reported that myopia patients were 60% more likely to have glaucoma than emmetropic persons [31]. Similarly, the incidence of myopia in open angle glaucoma, low-tension glaucoma and ocular hypertension is also high [32]. Moderate and especially high myopia is considered a risk factor for the development and the progression of glaucoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in Wisconsin reported that myopia patients were 60% more likely to have glaucoma than emmetropic persons [31]. Similarly, the incidence of myopia in open angle glaucoma, low-tension glaucoma and ocular hypertension is also high [32]. Moderate and especially high myopia is considered a risk factor for the development and the progression of glaucoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, myopia has been confirmed as a risk factor for glaucoma development in many publications including in large-scale population-based studies, but has not been confirmed as a risk factor for progression. 22,[27][28][29][30] Some studies even reported protective effect of myopia against glaucoma progression. 31 Here, we aimed to test the hypothesis that thinner ONH may be a risk factor for glaucoma progression.…”
Section: Discussionmentioning
confidence: 96%
“…83,89 Myopia may coexist in 3 to 18% of patients with glaucoma. 90 The association between high myopia (>10 diopters [D]) and glaucoma is particularly significant (p < .001). Some of the high myopia-related factors implicated in the development of glaucoma are a structurally weak optic nerve in myopia, impaired aqueous outflow, choroidal vascular changes, strong familial tendency, and angle malformation.…”
Section: What Are the Demographic Characteristics Of Patients With Poag?mentioning
confidence: 99%